2014
DOI: 10.1098/rstb.2013.0299
|View full text |Cite
|
Sign up to set email alerts
|

How arbitrary is language?

Abstract: It is a long established convention that the relationship between sounds and meanings of words is essentially arbitrary—typically the sound of a word gives no hint of its meaning. However, there are numerous reported instances of systematic sound–meaning mappings in language, and this systematicity has been claimed to be important for early language development. In a large-scale corpus analysis of English, we show that sound–meaning mappings are more systematic than would be expected by chance. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
278
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(323 citation statements)
references
References 51 publications
10
278
7
Order By: Relevance
“…Furthermore, in a large-scale corpus analysis, Monaghan et al [34] demonstrated that sound-meaning mappings in the English lexicon are more systematic than would be expected by chance. That is, subtle sound symbolism, which people do not consciously detect, may exist throughout the conventional (i.e.…”
Section: Sound Symbolism Is Not Peripheral In Modern Languagementioning
confidence: 99%
“…Furthermore, in a large-scale corpus analysis, Monaghan et al [34] demonstrated that sound-meaning mappings in the English lexicon are more systematic than would be expected by chance. That is, subtle sound symbolism, which people do not consciously detect, may exist throughout the conventional (i.e.…”
Section: Sound Symbolism Is Not Peripheral In Modern Languagementioning
confidence: 99%
“…Many past studies on the relationship between form and meaning in language (Shillcock et al, 2001;Monaghan et al, 2014;Gutiérrez et al, 2016;Dautriche et al, 2017) mitigated this concern by only considering monomorphemic words, discarding a large fraction of the lexicon in the process.…”
Section: Methodsmentioning
confidence: 99%
“…This is illustrative of the point to follow, that most words contain a combination of arbitrary, systematic, and iconic elements. We chose fun because of its low iconicity rating (Winter, Perry, Perlman, & Lupyan, 2017) and derived systematicity value (Monaghan, Shillcock, Christiansen, & Kirby, 2014). Its length is also atypical of abstract nouns, which tend to be longer than concrete ones (Reilly & Kean, 2007), though this raises the interesting question of whether antisystematic words are arbitrary.…”
Section: Arbitrariness and Nonarbitrarinessmentioning
confidence: 99%